Clavicle fractures - one of the painful injuries in sports - Łoś, Dawid; Nowak, Aleksandra; Janus, Anita; Kaptur, Agata; Dziedziński, Dawid; Kwaśniewska, Oliwia (Quality in Sport, 2024)
Introduction Clavicle fractures can be treated either surgically or non-operatively. Traditionally, displaced fractures of the clavicle shaft in adults have been treated non-operatively. However, recent evidence suggests that the rate of non-union following non-operative treatment is higher than previously thought. In addition, there is a growing body of literature suggesting better functional outcomes with operative treatment. This shift in understanding has led to an increased preference for operative management of these fractures in recent years. The aim of this review is to summarise the current evidence on the management of clavicle fractures. Review methods English-language scientific literature found in PubMed and Google Scholar was used for the review. Articles were searched based on keywords. Each article was analyzed for knowledge currency and relevance for use in the review. Description of the State of Knowledge After searching the articles, 20 articles were selected for final analysis. The collected data provided the latest information on clavicle fractures regarding the epidemiology, treatment and its results. Summary Clavicle fractures are one of the injuries happening in sports. As the surgical techniques become better overtime, the dilemma regarding invasive versus non-invasive treatment appears. Overall, both these approaches yield similar results, however may be suitable for different individuals.